64.16.2 problem 2

Internal problem ID [13605]
Book : Differential Equations by Shepley L. Ross. Third edition. John Willey. New Delhi. 2004.
Section : Chapter 7, Systems of linear differential equations. Section 7.1. Exercises page 277
Problem number : 2
Date solved : Tuesday, January 28, 2025 at 05:53:47 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x \left (t \right )+\frac {d}{d t}y \left (t \right )-x \left (t \right )&=-2 t\\ \frac {d}{d t}x \left (t \right )+\frac {d}{d t}y \left (t \right )-3 x \left (t \right )-y \left (t \right )&=t^{2} \end{align*}

Solution by Maple

Time used: 0.036 (sec). Leaf size: 32

dsolve([diff(x(t),t)+diff(y(t),t)-x(t)=-2*t,diff(x(t),t)+diff(y(t),t)-3*x(t)-y(t)=t^2],singsol=all)
 
\begin{align*} x \left (t \right ) &= -2+{\mathrm e}^{-t} c_{1} \\ y \left (t \right ) &= -t^{2}+4-2 \,{\mathrm e}^{-t} c_{1} -2 t \\ \end{align*}

Solution by Mathematica

Time used: 0.074 (sec). Leaf size: 98

DSolve[{D[x[t],t]+D[y[t],t]-x[t]==-2*t,D[x[t],t]+D[y[t],t]-3*x[t]-y[t]==t^2},{x[t],y[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} x(t)\to -\frac {1}{4} \int _1^t-4 e^{K[1]-t} K[1] (K[1]+4)dK[1]-t^2-2 t-\frac {c_1 e^{-t}}{4} \\ y(t)\to \frac {1}{2} \left (\int _1^t-4 e^{K[1]-t} K[1] (K[1]+4)dK[1]+c_1 e^{-t}\right )+t^2+2 t \\ \end{align*}